Eu voto, porque eu gosto: análise do comportamento eleitoral de idosas em Fortaleza-CE - Marques, Carla Beatriz Raulino (2018)
The objective of this research was to apprehend the polítical behavior of elderly voters, residents of Fortaleza, and mainly to investigate whether older women like to vote. The research took place in two stages: qualitative and quantitative. Initially, focus groups and interviews were conducted in two entities that provide services to the elderly. One serves poor people, another presents a middle-class audience. Next, 427 questionnaires were administered, with elderly women of different social classes, distributed in 39 neighborhoods of the capital of Ceará. The theories that guided this investigation are those referring to the elderly woman (concept of old age, gender and generation) and to polítical behavior (polítical socialization, polítical culture and electoral behavior). The elderly voter presents particularities for being elderly, for being a woman and for belonging to a different generation. Polítical socialization consists in the assimilation of values, thoughts and polítical behaviors. These embodied contents tend to remain in the adult phase, however, as the subjects grow older and enter into different generations, they come into contact with new socializing processes, and therefore can acquire new polítical attitudes. In this way, polítical socialization and changes in the life cycle, coupled with gender and socioeconomic inequalities, can modify the electoral behavior of the subjects. The data collected demonstrate several trends in the polítical behavior of the elderly women, and especially confirms the hypothesis that they mostly like to vote, because they consider this an important act. It is concluded that the majority of women enjoy voting, because they want to contribute to the construction of a better society, and they see the day of the election as joyful, due to the meetings with relatives and friends that the day of the election makes possible.